Application of Fusarium sp. immobilized on multi-walled carbon nanotubes for solid-phase extraction and trace analysis of heavy metal cations. (30th August 2020) - Moallaei, Hossein; Bouchara, Jean-Philippe; Rad, Abolfazl; Singh, Pardeep; Raizada, Pankaj; Tran, Hai Nguyen; Zafar, Muhammad Nadeem; Giannakoudakis, Dimitrios A.; Hosseini-Bandegharaei, Ahmad
Highlights: Fusarium sp. isolated from toenail onychomycosis was immobilized on MWCNTs. The biocomposite had a high performance in SPE of some heavy metals before determination by ICP-OES. The new SPE method was robust enough to tackle reference samples with highly complex matrices. The method was successful when applied to trace determination of analytes in food samples. Abstract: In the present work, for the first time, the filamentous fungus Fusarium sp. was utilized for devising a novel method for pre-concentration and determination of trace amounts of Pb(II), Cu(II), Cd(II), and Zn(II) ions, using a mini-column packed with Fusarium -coated multi-walled carbon nanotubes and inductively coupled plasma-optical emission spectrometry. Optimal analytical conditions including pH, ionic strength, elution solution, sample and eluent flow rates, and sample volume were determined. The detection limits were 0.39, 0.060, 0.021, and 0.025 ng mL −1 for Pb(II), Cu(II), Cd(II), and Zn(II) cations, respectively. This new method demonstrated a high performance for the analytes, and their adsorption was not affected by the different co-existing ions. The present procedure was validated by the analysis of standard reference materials, since the obtained data were in close agreement with reference values. Finally, this new procedure was successfully applied to analysis of heavy metal cations in natural food and water samples.